Heterodox central bankers: Eccles, Prebisch and financial reform in 1930s - Esteban Pérez Caldentey; Matías Vernengo (The University of Utah, Department of Economics, 2012)
The Great Depression led to a need to rethink the principles of central banking, as much as it had led to the rethinking of economics in general, with the Keynesian Revolution at the forefront of the theoretical changes. This paper suggests that the role of the monetary authority as a fiscal agent of government and the abandonment of the view of the economy as self-regulated were the central changes in central banking in the center. In addition, in the periphery central banks changed to try to insulate the worst effects of balance of payments crises and the use of capital controls became more common. Marriner S. Eccles, in the United States, and Raúl Prebisch, in Argentina, are paradigmatic examples of those new tendencies of central banking in the 1930s.
Keywords: B31; B50; E58; N10; 330; Monetary Policy; Economic History; Heterodox Economics